2019
DOI: 10.1071/rd18217
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress induces heat shock protein 70 and apoptosis during embryo development in a Neotropical freshwater fish

Abstract: Fish embryos are particularly vulnerable to temperature changes, with the effects varying with developmental stage. The major aim of the present study was to analyse the relationship between apoptosis and heat shock protein (HSP) 70 during embryo development under thermal stress conditions. To this end, Prochilodus lineatus embryos at the blastopore closure stage were subjected to one of three thermal treatments for 1h (Group 1, 25°C (control); Group 2, 20°C; Group 3, 30°C) and then examined at 0, 4 and 8h pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Besides heat stress (Baena et al, 2018; Sales et al, 2018), heat shock proteins (HSP) are being evaluated in apoptosis, oxidative stress, inflammatory diseases, cancer (Ikwegbue et al, 2017), virus infection (Shan et al, 2018), bacterial infection (Kim et al, 2018), as immunomodulators (Edkins et al, 2017; Zininga et al, 2018), therapeutics (Skórzynska-Dziduszko et al, 2018), and diagnostics (Lechner et al, 2018; Tang T. et al, 2018). HSPs have diagnostic role in ischemic injury of cardiomyocytes (Santos et al, 2018), inflammatory process of multiple sclerosis (Lechner et al, 2018), early diagnosis of lung cancer (Tang T. et al, 2018), proteome stress (Liu and Zhang, 2018), bipolar disorder (Cheng et al, 2018), and anti-apoptotic agent (Jang et al, 2018).…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
“…Besides heat stress (Baena et al, 2018; Sales et al, 2018), heat shock proteins (HSP) are being evaluated in apoptosis, oxidative stress, inflammatory diseases, cancer (Ikwegbue et al, 2017), virus infection (Shan et al, 2018), bacterial infection (Kim et al, 2018), as immunomodulators (Edkins et al, 2017; Zininga et al, 2018), therapeutics (Skórzynska-Dziduszko et al, 2018), and diagnostics (Lechner et al, 2018; Tang T. et al, 2018). HSPs have diagnostic role in ischemic injury of cardiomyocytes (Santos et al, 2018), inflammatory process of multiple sclerosis (Lechner et al, 2018), early diagnosis of lung cancer (Tang T. et al, 2018), proteome stress (Liu and Zhang, 2018), bipolar disorder (Cheng et al, 2018), and anti-apoptotic agent (Jang et al, 2018).…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
“…Numerous studies have shown that apoptosis in fish cells occurs after exposure to heat stress [38]. Heat stress at the blastopore closure stage increases caspase3-mediated apoptosis in P. lineatus embryos [12]. One study revealed that the level of apoptosis in the Pikeperch (Sander lucioperca) liver tissue significantly increased with rising temperature [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, severe apoptosis can also lead to tissue and organ damage and abnormal function [11]. Although heat stress has been shown to induce apoptosis in fish such as Prochilodus lineatus [12], Paralichthys olivaceus [13], and Takifugu obscurus [14], there are few reports on the effects of heat-stress-induced apoptosis in sturgeon.…”
Section: Introductionmentioning
confidence: 99%
“…HSP70 expression in cold‐shocked rohu ( Labeo rohita Hamilton 1822; 26 to 4°C for 3 h) was most elevated in the spleen and liver, and also in the kidney and muscle with respect to a control group (Giri et al ., 2014). In another freshwater tropical species, juvenile streaked prochilod ( Prochilodus lineatus Valenciennes 1837), HSP70 abundance was initially depressed following transfer from 25 to 20°C water for 1 h, but by 4 h HSP70 abundance was elevated above baseline levels (Sales et al ., 2019). Relative to an ambient control (16°C), kaluga sturgeon ( Huso dauricus Georgi 1775) cold shocked at 4 or 10°C for 2 h displayed elevated transcription levels of HSP70 in muscle and liver tissues at 4°C and in the gills at both temperatures, whereas HSP90 transcription was elevated in the liver at 4°C and in the muscle and gills at both temperatures (Peng et al ., 2016).…”
Section: Cold Stress and The Generalized Stress Response In Fishmentioning
confidence: 99%